2021
DOI: 10.1063/5.0044822
|View full text |Cite
|
Sign up to set email alerts
|

An ultrafast vibrational study of dynamical heterogeneity in the protic ionic liquid ethyl-ammonium nitrate. I. Room temperature dynamics

Abstract: This is a copy of the published version, or version of record, available on the publisher's website. This version does not track changes, errata, or withdrawals on the publisher's site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Usually, 1/3 T or –1 does not contribute much to T Hom –1 , so we think this is a reasonable approximation for convenience, though model fitting to polarization-dependent spectra to fit T or has been done. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Usually, 1/3 T or –1 does not contribute much to T Hom –1 , so we think this is a reasonable approximation for convenience, though model fitting to polarization-dependent spectra to fit T or has been done. 32 …”
Section: Resultsmentioning
confidence: 99%
“…T or −1 doesn't contribute much to T hom −1 , so we think this is a reasonable approximation for convenience, though model fitting to polarization dependent spectra to fit T or has been done. 17 For comparison, we also analyze the simulated data using the center-line-slope (CLS) method. 12,13 One feature of 2D Kubo lineshapes is that they are asymmetric in frequency and the asymmetry is, itself, frequency dependent (see Figure S1).…”
Section: A Fitting Simulated Datamentioning
confidence: 99%
“…This manuscript provides a comprehensive study of how fitting generalized Kubo lineshapes to multidimensional spectra compares to the CLS method in terms of the accuracy, precision and reliability of the resulting parameters. While Garret-Roe and coworkers have shown several examples of model fitting 2D IR waiting-time series using the fmincon function in MATLAB, [17][18][19][20] a comparison of accuracy between model fitting and the CLS method by fitting to simulated spectra, where true values of parameters are known, has been missing. We find our model fitting routine improves precision over the CLS method by 8× to 15× on average for Kubo time constants and 8× to 50× for Kubo amplitudes and homogeneous dephasing, which is due in part to a novel figure of merit used in our fitting algorithm that we refer to as the scale invariant gradient norm (SIGN).…”
Section: Introductionmentioning
confidence: 99%
“…In other work, Maroncelli's group showed that the C153 solvation times in several IL classes (imidazolium, ammonium, and phosphonium) follows a well-defined linear correlation with viscosity that was a linear extension of that observed in conventional dipolar solvents [24,25]. To date, the role that IL-IL and/or IL + cosolvent interactions play in modified IL solutions remains a topic interest [2,7,15,16,18,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…Dynamical measurements from extrinsic probes provides a useful perspective for determining the range of effects of the molecular interactions that govern probe-solvent interactions. In a very recent report, Garrett-Roe and coworkers identified two sub-ensembles in EAN from SCN − vibrational and rotational relaxation using 2-D IR spectroscopy, giving yet further evidence of the dynamical heterogeneity that is observed in ILs [43]. Given the inherent nanoheterogeneity within ILs and IL solutions, we set upon the task of evaluating whether hydrodynamic theory provided a good description against which we could assess probe rotational motion in the EAN/MeOH system.…”
Section: Introductionmentioning
confidence: 99%